Jojo Tulloh: The Modern Peasant: Adventures in City Food - Clark, Letitia (Petits Propos Culinaires, 2013)
Jojo Tulloh: The Modern Peasant: Adventures in City Food: Chatto & Windus, 2013, 320 pp., paperback, £12.99.